Tafazani's view of Al- Zamakhshari's isolationst views (Journal of Hama University, 2019)
This research has been shown the position of (Taftazani) the views of (AL-Zamakhshari) in his book (AL-Kashaf) and surat (AL-Imaran) and (Women) as a. model. I began the research with a linguistic definition of the meaning. Of (retirement) and its origin and the real founder of this retiring. Then the definition of both Zamakhshari and Taftazani and the doctrine of each of them has been a way to show the position of Taftazani of Zamakhshari by mentioning the verse in which Zamakhshari put his opinion, and then mentioned what Zamakhshari interpretation of this verse, and then the suspension of Taftazani on Zamakhshari whether or not. In some position.I mentioned the view of Ibn- AL-Munaeir, the owner of the (remedy) as on appendix to the View of Taftazani. This research has been concluded with some of results, which I find them.